Responsibility of international organizations: dispute settlement mechanisms under international law - Mamaladze, Ana (Riga Graduate School of Law, 2023)
This thesis explores the responsibility and accountability of international organizations under international law. It examines the challenges in determining the scope of liability and enforcing accountability and proposes measures to enhance the accountability framework. The study aims to ensure that international organizations uphold their legal commitments to promote a just and equitable international order. Through an analysis of relevant legal principles, mechanisms, and case studies, this research provides insights into the complexities surrounding the responsibility of international organizations. The findings highlight the need for effective enforcement mechanisms, improvements in the legal framework, and greater cooperation among member states.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; international organizations; Dispute Settlement